Green leadership and competence on employee performance through work engagement in public health centers - Setyorini, Winarti; Brahmasari, Ida Aju; Ratih, Ida Aju Brahma (Edelweiss Applied Science and Technology, 2026)
This study examines the influence of Green Leadership and Competence on Employee Performance, with Work Engagement as a mediating variable, in public health centers. In response to growing demands for sustainable leadership and workforce effectiveness in the healthcare sector, this research aims to identify key determinants of employee performance. A quantitative explanatory approach was employed, involving 215 respondents from public health institutions. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that Green Leadership and Competence have a significant positive effect on Employee Performance. Competence significantly influences Work Engagement, whereas Green Leadership does not. Furthermore, Work Engagement does not significantly affect Employee Performance and therefore does not mediate the relationship between the independent and dependent variables. These results emphasize the importance of leadership practices and employee competence in enhancing performance within the public healthcare sector. Practical implications include strengthening competence development and promoting sustainable leadership practices. This study is limited by its cross-sectional design and focus on a single sector. Future research is encouraged to incorporate additional mediating or moderating variables to further explore these relationships.